Pengaruh Kebijakan Dividen, Kebijakan Utang, dan Kinerja Keuangan Terhadap nilai perusahaan (Studi Empiris Perusahaan Teknologi dan Transportasi yang terdaftar di Bursa Efek Indonesia Tahun 2018-2022) - Dwi Alditia Aryanda (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
This study aims to determine the influence of Dividend Policy, Debt Policy, and Financial Performance on Company Value in Technology and Transportation companies listed on the Indonesia Stock Exchange for the 2018-2022 period. Based on the purposive sampling method, a sample of 10 companies was obtained. The analysis method used is a descriptive statistical method using a panel data regression analysis tool. The results of this study show that (1) Dividend policy has no effect on company value, (2) Debt policy has a significant effect on company value, (3) Financial performance has no effect on company value.